2013
DOI: 10.1111/ejed.12026
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diverse Institutions in Framing Adult Learning Systems

Abstract: This article considers the role of diverse institutions in framing adult learning systems. The focus is on institutional characteristics and configurations in different countries and their potential impact on the extent of adult learning, as well as on inequalities in access to adult learning. Typologies of education and training systems as well as labour market and welfare systems are introduced in relation to specific particularities relevant to adult learning. An emphasis is placed on how institutions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 59 publications
0
24
0
5
Order By: Relevance
“…Nevertheless, in both classifications, the Nordic countries stand out as being characterised by high levels of participation in higher education, lower social inequality, and strong public engagement in the funding of higher education. Saar et al (2013) present a classification of adult learning systems and link it to varieties of capitalism approach. However, neither the position nor any characteristics of higher education are clearly discussed in this classification.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Nevertheless, in both classifications, the Nordic countries stand out as being characterised by high levels of participation in higher education, lower social inequality, and strong public engagement in the funding of higher education. Saar et al (2013) present a classification of adult learning systems and link it to varieties of capitalism approach. However, neither the position nor any characteristics of higher education are clearly discussed in this classification.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…So far, we know only little about institutional influences on the inequality in access to further training among adults (Bills and van de Werfhorst 2018;Saar et al 2013). There is ample evidence for cross-national differences in levels of training participation.…”
Section: Previous Researchmentioning
confidence: 99%
“…Furthermore, the influence of institutions continues after schooling is finished. The literature about institutional influences on training participation among adults showed that there are systematic differences between countries both in the level and in the inequality of training (Saar et al 2013;Bills and van de Werfhorst 2018). Yet, little is known so far about the international variation in the effect of tasks on further training participation.…”
Section: Introductionmentioning
confidence: 99%
“…The origins of these FIGURE 6. A European Lifelong Learning Index Source: Hoskins et al (2010) 366 European Journal of Education differences can be found in the institutional models linking education, welfare and employment systems: some of them inherited from the Communist past, some of them emerging from the transformation process and the specific market economy model adopted by the countries (Szelenyi & Wilk, 2010;Saar et al, 2013). In this respect, the Baltic States, the four Visegrád Countries, and the countries of the Western and Eastern Balkans form four distinct patterns.…”
Section: Evaluating the Outcomesmentioning
confidence: 99%